Analysis of phytochemical, antioxidant, and α-amylase inhibition capacity of methanol extract of six plants from Kaski, Gulmi and Rupandehi districts of Nepal - Subba, Bimala; Subedi, Namrata; Parajuli, Sanju (BIBECHANA, 2023)
This study was designed to explore phytochemicals and biological activities of methanolic extract of six traditional medicinal plants (Clerodendrum trichotomum, Mallotus philipinensis, Dioscorea-bublifera, Rubia cordifolia, Viscum articulatum) of Nepalese origin. Plant extracts were prepared in methanol through cold percolation. Analysis of phytochemical constituent, antioxidant capacities and brine shrimp lethality assay of the test plant samples were carried out using standard methods. The 1,1-diphenyl-2-picryl hydrazyl (DPPH) method was used to study antioxidant activity of different plant extracts. Furthermore, starch-iodine method was used to study the inhibition effect of extract on α-amylase. Phytochemical analysis showed the presence of phytochemicals like alkaloids, flavonoids, phenolic content, glycosides, reducing sugars, etc. in six medicinal plants. Brine shrimp lethality assay suggested the presence of pharmacologically active compounds. Total phenolic content and total flavonoid content of C. trichotomum’s leaves extract were found to be higher with 212.742 mg GAE/g and 112 mg Q/g respectively with strong antioxidant activity. Similarly, the α-amylase inhibition of R. cardifolia’s root extract and C. trichotomum‘s leaves extract was found to be 252.44±0.55 µg/mL and 293.33± 0.81 µg/mL comparative with IC50 value 119.063±0.73 µg/mL of standard acarbose that showed remarkable antidiabetic property among six samples. The results, obtained here suggested that six medicinal plants i.e. C. trichotomum, M. philipinensis, D. deltoidea, D. bublifera, R. cordifolia, and V. articulatum, Nepal origin showed biological activity by targeting multiple drug targets which justifies their traditional uses. This is the first finding that C. trichotomum‘s leaves can be a promising source for the development of natural antioxidant and antidiabetic agents.